(untitled) (International Journal of Physiotherapy, 2019)
Background: Being overweight is a risk factor in developing many chronic diseases, and globally, the frequency of obesity rapidly increases. Our study aims to investigate the effects of an exercise program on Body Mass Index (BMI) and fasting blood glucose (FBG) level in overweight and obese subjects who have a diet program. Methods: 61 overweight and obese women subjects were included in this study. The subjects were randomly divided into two groups. The Control Group (CG) was included 32 women and received only a diet program. And, Experimental Group (EG) was included 29 women and received both diet and exercise program. A dietitian recorded weight, height, and BMI, and fasting blood glucose levels were recorded by blood test asking from subjects before and after program. Results: There was statistically significant decrease in BMI in both groups (p<0,05). When the CG and the EG group were compared, there was more decrease in the EG group. Fasting blood glucose level decreased statistically significantly in the exercise and diet groups (p <0.05). When the mean changes between the groups were compared, the difference in the FBG level in the exercise and diet groups was not statistically found even though it was higher than the dietary group. Conclusion: The 6-week exercise program which was applied in addition to diet programs for overweight and obese people led to improvement in BMI and FBG level, we think that a multidisciplinary team should follow these people.